Bronchial or Laryngeal Obstruction Induced by Exercise? - Ayoub Bey; Sophie Botti; Laurianne Coutier-Marie; Claude Bonabel; Claude Bonabel; Stéphanie Metche; Silvia Demoulin-Alexikova; Silvia Demoulin-Alexikova; Cyril Etienne Schweitzer; Cyril Etienne Schweitzer; Cyril Etienne Schweitzer; François Marchal; et al. (Frontiers Media S.A., 2017)
A child suspected of exercise-induced laryngeal obstruction and asthma is examined by laryngoscopy and respiratory resistance (Rrs) after exercise challenge. Immediately at exercise cessation, the visualized adduction of the larynx in inspiration is reflected in a paroxystic increase in Rrs. While normal breathing has apparently resumed later on during recovery from exercise, the pattern of Rrs in inspiration is observed to reoccur following a deep breath or swallowing. The procedure may thus help diagnosing the site of exercise-induced obstruction when laryngoscopy is not available and identify re-inducers of laryngeal dysfunction.